Analysis on the Masterplan Model of Street Children Handling - Soetji Andari (Jurnal Penelitian Kesejahteraan Sosial, 2016)
The existence of street children in various areas need special handling, problems related with them are education, abandonment, violence, discrimination and child labor. The local government of Sleman Regency initiates street children handling through a masterplan made through assessment, focus group discussion held with stakeholders related to street children handling, and comparative study in order to make a coprehensive masterplan. The research uses qualitative descriptive approach. Data are gathered throuh interviews with numbres of street children, stakeholders related to street children (government and non-government), and street children guides. The masterplan is designed to handle and overcome streetchildren problems totally, coordinated, continue, and functioned as guidance for stakeholders related to children issues having the same perception toward street children.